Perawatan Kesehatan Anak Melalui Posyandu Remaja Di LPKA Kelas II Bengkulu - Imansyah Putra; Herry F Butar-Butar (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of the Youth Posyandu program at the Bengkulu Class II Special Development Institute (LPKA) as an effort to fulfill the health rights of fostered children. The problems faced include the lack of understanding of fostered children regarding the importance of reproductive health and healthy behavior, as well as challenges in implementing programs that do not involve all fostered children. The method used is a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. Primary data sources were obtained from foster children and LPKA officers, while secondary data came from official documents, books, and related journals. The data obtained was analyzed using triangulation techniques to increase validity and understand the phenomenon holistically. The results showed that the Posyandu Remaja program has been running quite effectively in providing basic health services and reproductive health education, although there is a gap between the number of foster children who participate in the program and those who need these services. This program also plays an important role in increasing the knowledge of foster children related to nutrition, mental health, and prevention of drug abuse. However, the participation of foster children is still limited, especially in terms of reproductive health counseling. Collaboration between LPKA, Puskesmas, and related agencies needs to be strengthened to ensure the program is more inclusive and sustainable.